Evaluation of Non-HIV-Related, Drug-Sensitive Cluster Outbreaks of Tuberculosis with PCR-based DNA Fingerprinting. Issue 5 (3rd October 1996) - FitzGerald, JM; Black, WA; Kunimoto, D
Abstract : OBJECTIVES: To characterize two cluster outbreaks of tuberculosis by DNA fingerprinting and to evaluate the possibility of their association with human immunodeficiency virus (HIV) infection and multiple drug-resistant Mycobacterium tuberculosis . SETTING: Two clusters of tuberculosis cases in adjoining aboriginal Canadian reserves and a control population. METHODS: All cases of tuberculosis diagnosed in the two communities and a number of control isolates were fingerprinted using a novel simplified DNA-based technique. Demographic data, purified protein derivative (PPD) skin test response to 5TU PPD, type of disease and HIV serology were also evaluated. Positive cultures were assessed for susceptibility to antituberculous drugs. RESULTS: Two distinct clusters with five cases in one community and 21 cases in the second were identified. Isolates from both communities differed in their DNA pattern but were identical within communities. Thirteen cases had bacteriologically proven disease and grew susceptible organisms. Serological analysis for HIV infection was carried out in 15 of 18 adults, and all were negative. CONCLUSIONS: The study shows the potential for the rapid transmission of tuberculosis infection in HIV-negative subjects with susceptible organisms. It further highlights the usefulness of DNA fingerprinting for molecular epidemiology in evaluating particular outbreaks.